Sea urchin utilisation in Eastern Indonesia - Tamti, Hartati; Ambo-Rappe, Rohani; Bin Andy Omar, Sharifuddin; Pagalay, Budimawan; Iqram, Muhammad; Renema, Willem; Moore, Abigail Mary (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Sea urchins have long been an important component of gleaning invertebrate fisheries and are valued for their highly nutritious gonads. Sea urchin fisheries are often unreported and unregulated, despite increasing indications of overexploitation. Data on the post-harvest utilization of sea urchins are limited, particularly in the Indo-Pacific region. This study at 12 sites across four regions in Indonesia (Sulawesi, Moluccas, Nusa Tenggara, Papua) aimed to provide an overview of sea urchin utilization in eastern Indonesia. Data were collected from July to September 2020 using a questionnaire with a snowballing sampling method. There were 187 respondents (62.6% male and 37.4% female) ranged in age from 3-76 years old, and most had been collecting sea urchins for more than five years. Respondents mostly collected the sea urchins from coral reef or seagrass habitats. Four genera (Tripneustes, Diadema, Echinometra and Echinothrix) were identified. Mean catch ranged from 32 (Makassar) to 169 (Maluku Tengah) individual sea urchin per collection. Most respondents knew local names for sea urchins, especially those they collected. Almost 70% respondents used their catch mainly for home consumption, and only 4.8% respondents mainly selling their catch. Most urchins sold were whole or crudely de-spined, typically fetching IDR 500-1000 each. Additional post-harvest processing before sale included removing the gonads from the test and/or cooking, with a unit price of IDR 5,000-25,000/product. Commonly consumed raw, urchins were sometimes cooked (mostly barbecued). These data indicate a need for efforts towards socio-ecologically appropriate sea urchin conservation and fisheries management to address the widespread indications of increasing exploitation levels and declining sea urchin populations.